PouC Regulates Expression of bmp4 During Atrioventricular Canal Formation in Zebrafish. Issue 2 (10th December 2018) - Bhakta, Minoti; Padanad, Mahesh S.; Harris, John P.; Lubczyk, Christina; Amatruda, James F.; Munshi, Nikhil V.
Abstract : Background: Many human gene mutations have been linked to congenital heart disease (CHD), yet CHD remains a major health issue worldwide due in part to an incomplete understanding of the molecular basis for cardiac malformation. Results: Here we identify the orthologous mouse Pou6f1 and zebrafish pouC as POU homeodomain transcription factors enriched in the developing heart. We find that pouC is a multi‐functional transcriptional regulator containing separable activation, repression, protein–protein interaction, and DNA binding domains. Using zebrafish heart development as a model system, we demonstrate that pouC knockdown impairs cardiac morphogenesis and affects cardiovascular function. We also find that levels of pouC expression must be fine‐tuned to enable proper heart formation. At the cellular level, we demonstrate that pouC knockdown disrupts atrioventricular canal (AVC) cardiomyocyte maintenance, although chamber myocyte specification remains intact. Mechanistically, we show that pouC binds a bmp4 intronic regulatory element to mediate transcriptional activation. Conclusions: Taken together, our study establishes pouC as a novel transcriptional input into the regulatory hierarchy that drives AVC morphogenesis in zebrafish. We anticipate that these findings will inform future efforts to explore functional conservation in mammals and potential association with atrioventricular septal defects in humans. Developmental Dynamics 248:173‐188, 2019. © 2018 Wiley Periodicals, Inc. Key Findings: Identified pouC as a novel POU homeodomain transcription factor expressed in zebrafish heart. Demonstrated that pouC functions as a multi‐functional transcriptional regulator. Showed that pouC plays a role in atrioventricular canal morphogenesis during heart development. Established bmp4 as a direct transcriptional target of pouC.